NHSE Regional International Medical Graduates Conference for Yorkshire and Humber School of Psychiatry - Christiana Elisha-Aboh; Anilkumar Pillai; Nazish Hashmi; Senaka Weerakoon; Theresa Ugalahi (BJPsych Open)
Aims: International Medical Graduates (IMGs) represent over 30% of the NHS workforce. They play a vital role in addressing healthcare shortages and enhancing cultural diversity. They are a significantly mixed group in terms of their experience, skills and overall development. Due to differing systems, IMGs often require additional support. The right support ensures that they achieve their professional goals, highlighting the need for targeted conferences.